Fully Distributed Consensus Voltage Restoration Control Based on Dynamic Event-Triggered Mechanisms for Offshore Wind Power Systems - Chen, Dawei; Zeng, Zhijie; Tian, Ye; Wang, Chenyu; Xiao, Jun; Lin, Xiaoqing (Energies (Basel), 2025)
Although voltage regulation in distributed generation (DG) in offshore wind power systems has been deeply studied, information on the global communication network structure and high communication bandwidths still remain key factors restricting the integration of a high proportion of new energy sources. In order to achieve precise voltage regulation while reducing communication, this paper proposes a fully distributed dynamic event-triggered secondary voltage restoration control for offshore wind power systems. Firstly, the nonlinear system model is switched to the linear second-order multi-agent system (MAS) by feedback linearization. This is a crucial step for the subsequent research. From there, a fully distributed voltage restoration control strategy is proposed, which utilizes adaptive event-triggered protocol. The proposed protocol operates independently of global information. Finally, the effectiveness of the control protocol is verified through simulation.